The Study of Consumer Preferences and Advertising Effectiveness Analysis Towards Studio Hikari Instagram Story Video Ads - Dovan Fakhradyan (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2021)
Currently, one of the fastest-growing platforms for advertisement is Instagram stories. With this relatively new format, Studio Hikari is having difficulties in developing an effective advertisement for its Instagram stories. This research aims to understand factors that influence viewer preferences toward Instagram stories advertisement, assess the Instagram story advertising effectiveness, and give recommendations to Studio Hikari regarding their upcoming advertisement in an Instagram story. This study was conducted with an online survey method, to test the advertising preferences and effectiveness of 7 different planned Instagram story advertisements from Studio Hikari that has a unique combination of three variables (duration, color of background, level of informativeness). The result of this study shows that the most preferred combination is the Instagram story with a duration of 15 seconds, yellow background color, and a medium level of informativeness. For advertising effectiveness, it is found that there is a significant difference between ad effectiveness and the 7 Instagram stories advertisement. The limitations of this research are that the number of variables tested are limited, which is only 3 variables, and all of the respondents are Studio Hikari's target market.